Investigation Of Process Time-Delay On Polyimide With Different Thicknesses For Photolithography Process - Ang , Karen Huei Ling (2011)
Polyimides (PI), particularly photosensitive polyimide (PSPI) has wide applications in semiconductor industries due to their good thermal, mechanical and chemical properties. During photolithography process, there might be time delays from coat to expose and from expose to develop. The time delay could change the profile of the structures and residues of precursor might leave on the film. In Infineon technologies, those wafers are scrapped if time delay exceeded 5 hours and every scrapped cost RM37500. As such, a study is carried out to investigate the effect of time delay in photolithography process to the cured polyimide film.